Cutting EDGE: intermediate students'BOOK with DVD-ROM - Cunningham, S. Sarah (Pearson Education Limited, 2013)
Cutting Edge Third Edition builds on the distinctive task-based approach that has made this course so popular. Engaging texts, new video content and a comprehensive digital package are just some of the features that make this fully revised edition even more effective. The brand-new World culture lessons encourage learners to explore contemporary topics and develop online research skills. Language live lessons provide light-hearted contexts for practising functional language and writing. The Students' DVD-ROM contains all the audio and video clips and a digital Mini Dictionary of key vocabulary.